PERANAN PENTADIO RESORT DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KABUPATEN GORONTALO - Hiola, Yustina (JSAP : Journal Syariah and Accounting Public, 2019)
This research aims to find out the management of pentadio resort attractions. The research method uses a qualitative type. Management of pentadio resort attractions in planning aspects is not optimal. This can be seen from the less planned arrangement of tourist attractions. Management of pentadio resort attractions in the organizing aspect is not optimal. This can be seen from the irregularities of the officers in the work such as the absence of uniformity in dress, and the many facilities that no longer function. Management of pentadio resort attractions in aspects of supervision is not optimal. This can be seen from the many tourist facilities that are not maintained anymore and just left.